The first DNA-supported record of Platicrista angustata (Eutardigrada, Hypsibiidae) from Germany and reply to Scheirer et al. (2024) - Piotr Gąsiorek (Evolutionary Systematics)
The recent paper of Gąsiorek et al. (2024a), containing integrative redescriptions of several taxonomically important hypsibiid species, provided necessary discriminative criteria used in modern eutardigrade identification. Herein, I present first DNA-backed, reliable record of a rare species Platicrista angustata from the German Taunus mountains. I also indicate that statements of Scheirer et al. (2024) are completely unfounded and result from the general lack of understanding what Gąsiorek et al. (2024a) wrote. Moreover, Scheirer et al. (2024) introduced new mistakes and misconceptions regarding Platicrista. Consequently, I provide a concise and full diagnosis of the genus Platicrista.